Effects of BI 655064, an antagonistic anti-CD40 antibody, on clinical and biomarker variables in patients with active rheumatoid arthritis: a randomised, double-blind, placebo-controlled, phase IIa study. Issue 6 (22nd March 2019) - Visvanathan, Sudha; Daniluk, Stefan; Ptaszyński, Rafał; Müller-Ladner, Ulf; Ramanujam, Meera; Rosenstock, Bernd; Eleftheraki, Anastasia G; Vinisko, Richard; Petříková, Alena; Kellner, Herbert; Dokoupilova, Eva; Kwiatkowska, Brygida; et al.
Abstract : Objective: To evaluate the safety, efficacy and therapeutic mechanism of BI 655064, an antagonistic anti-CD40 monoclonal antibody, in patients with rheumatoid arthritis (RA) and an inadequate response to methotrexate (MTX-IR). Methods: In total, 67 patients were randomised to receive weekly subcutaneous doses of 120 mg BI 655064 (n=44) or placebo (n=23) for 12 weeks. The primary endpoint was the proportion of patients who achieved 20% improvement in American College of Rheumatology criteria (ACR20) at week 12. Safety was assessed in patients who received at least one dose of study drug. Results: At week 12, the primary endpoint was not met, with 68.2% of patients treated with BI 655064 achieving an ACR20 vs 45.5% with placebo (p=0.064); using Bayesian analysis, the posterior probability of seeing a difference greater than 35% was 42.9%. BI 655064 was associated with greater changes in CD40–CD40L pathway-related markers, including reductions in inflammatory and bone resorption markers (interleukin-6, matrix metalloproteinase-3, receptor activator of nuclear factor-κB ligand), concentration of autoantibodies (immunoglobulin [Ig]G rheumatoid factor [RF], IgM RF, IgA RF) and CD95+ activated B-cell subsets. No serious adverse events (AEs) related to BI 655064 treatment or thromboembolic events occurred; reported AEs were mainly of mild intensity. Conclusion: Although blockade of the CD40–CD40L pathway with BI 655064 in MTX-IR patients with RA resulted in marked changes in clinical and biological parameters, including reductions in activated B-cells, autoantibody production and inflammatory and bone resorption markers, with a favourable safety profile, clinical efficacy was not demonstrated in this small phase IIa study. Trial registration number: NCT01751776